2008
DOI: 10.1021/jp710285x
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Reactions on a Au/Pd(111) Surface Alloy with Coadsorbed Chiral 2-Butanol and Propylene Oxide

Abstract: The coadsorption of R-and S-propylene oxide with R-2-butanol was studied on a dilute Au/Pd(111) alloy containing ∼8% gold using temperature-programmed desorption and reflection absorption infrared spectroscopy. Alloy formation strongly affects the surface chemistry of these molecules as compared to clean Pd(111). A portion of the propylene oxide decomposes to form CO and ethylidyne species on the alloy, while on clean Pd(111), it adsorbs reversibly. 2-Butanol reacts to form a 2-butoxide species on the alloy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…74 Although there are many examples of the formation of chiral structures on surfaces via functionalisation, the observation of their enantioselectivity still represents a challenge. 75,76 Inherently chiral metallic surfaces…”
Section: Chiral Surfaces Via Adsorptionmentioning
confidence: 99%
“…74 Although there are many examples of the formation of chiral structures on surfaces via functionalisation, the observation of their enantioselectivity still represents a challenge. 75,76 Inherently chiral metallic surfaces…”
Section: Chiral Surfaces Via Adsorptionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Industrially, the selective conversion of prochiral reagents to chiral products is a crucial step in the production of a variety of asymmetric pharmaceuticals. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Industrially, the selective conversion of prochiral reagents to chiral products is a crucial step in the production of a variety of asymmetric pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since Pasteur used tweezers to manually separate enantiopure crystals of sodium ammonium tartrate, 1 the idea of chirality has fascinated scientists. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Industrially, the selective conversion of prochiral reagents to chiral products is a crucial step in the production of a variety of asymmetric pharmaceuticals. While this feat is accomplished using either chiral catalysts or crystallization, many external influences have been shown to be capable of inducing such symmetry breaking, including circularly polarized light, [21][22][23] spin-polarized electrons, 24 and combinations of unpolarized light and magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the arena of chiral assembly, tartaric acid [2][3][4][5][6][7][8][9][10], cinchona alkaloids [11][12][13] and heptahelicene [14][15][16] are among the most commonly studied molecules. Several reports in the literature have revealed that chiral adlayers on achiral surfaces exhibit enantiospecific interactions with chiral probe molecules [17][18][19][20]. For example, (S)-propylene oxide exhibits a preference for adsorption on a Pt(111) surface modified with (S)-butoxide over an identical surface modified with (R)-butoxide, with the former system adsorbing 35% more of the probe molecule than the latter [18].…”
Section: Introductionmentioning
confidence: 99%